EFFECTS OF FEEDING FLAXSEED OIL ON PERFORMANCE AND SOME BLOOD BIOCHEMICAL TRAITS OF BROILER - Taher, Maisaa Ghany (Diyala Agricultural Sciences Journal, 2018)
This study was designed to evaluate the effect of the flaxseed oil on performance and some blood biochemical traits of broiler. Two equal treated groups (100 birds/treatment) with two replicates (50 birds/ replicate) of total 200 straight run (Ross 308) at age one day old chicks were randomly weighed and divided into two dietary treatments: T1 (as control group) birds fed basal diet without any additives. While, T2 fed diet supplemented daily with 0.6% flaxseed oil to the end of the experiment (42 days). Blood samples were collected and then analyzed. Parameters measured were total protein, cholesterol, serum GOT and GPT concentration. Results showed highly (p ≤ 0.01) significant differences in the weekly body weight and body weight gain between treatments. Feed conversion ratio recorded better values in (T2) compared with control group (T1). Also, birds fed 0.6% flaxseed oil had significantly (p ≤ 0.05) lower serum content of GPT and GOT (10.73 ± 0.50 and 98.54 ±3.45) respectively, and cholesterol concentration (176.0 ± 5.19) compared with control group (14.56 ± 0.70, 114.93 ± 2.93 and 217.5 ± 4.83) respectively. The results showed significantly (p ≤ 0.05) increased RBC count and PCV of chicks fed 0.6% flaxseed oil. However, there were no significant differences for WBC count and Hb between both treatments. In conclusion, flaxseed oil at a level of 0.6% in broilers diet led to enhance performance, blood biochemical parameters and health status of birds.